2021
DOI: 10.1152/ajpheart.00564.2020
|View full text |Cite
|
Sign up to set email alerts
|

No influence on tumor growth by intramuscular injection of adipose-derived regenerative cells: safety evaluation of therapeutic angiogenesis with cell therapy

Abstract: Therapeutic angiogenesis with autologous stem/progenitor cells is a promising novel strategy for treatment of severe ischemic diseases. Human clinical trials utilizing autologous adipose-derived regenerative cells (ADRCs) have not reported treatment-related critical adverse effects thus far. However, there is still a large knowledge gap whether treatment of ischemic diseases with angiogenic therapy using ADRCs would promote unfavorable angiogenesis associated with tumors in vivo. Herein, we addressed this clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…We consulted this case to the Accreditation Committee, and they determined that this event was unlikely to be related to the provision of regenerative strategy. In addition, our recent basic study has demonstrated that ADRC transplantation for a hind limb ischemia model in mice does not augment tumor-related angiogenesis or lymphangiogenesis for distant tumors, nor does it exacerbate tumor growth or metastasis [32]. Therefore, we consider that additional systemic screening tests for potential tumors will not be necessary for the TACT-ADRC protocols in the future.…”
Section: Discussionmentioning
confidence: 99%
“…We consulted this case to the Accreditation Committee, and they determined that this event was unlikely to be related to the provision of regenerative strategy. In addition, our recent basic study has demonstrated that ADRC transplantation for a hind limb ischemia model in mice does not augment tumor-related angiogenesis or lymphangiogenesis for distant tumors, nor does it exacerbate tumor growth or metastasis [32]. Therefore, we consider that additional systemic screening tests for potential tumors will not be necessary for the TACT-ADRC protocols in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Sections were then incubated with primary antibodies, anti‐LYVE‐1 (lymphatic vessel endothelial hyaluronan receptor 1) (1:125; Acris) or phospho‐Akt (or Protein kinase B) (Cell Signaling Technology, CST; number 4060, 1:400), and anti‐mouse podoplanin (1:250; R&D Systems) antibodies, at 4 °C overnight, followed by incubation with secondary antibodies, Alexa‐Fluor 488‐conjugated anti‐rabbit (1:1000; Thermo Fisher Scientific) and Alexa‐Fluor 594‐conjugated anti‐goat (1:1000; Thermo Fisher Scientific) antibodies, respectively, at room temperature for 1 hour. 19 , 20 , 21 The capillary density of lymphatic vessels was evaluated as LYVE‐1 and podoplanin double‐positive cells per field by previously established methods. 17 , 19 , 21 The nuclei were stained using 4′,6‐diamidino‐2‐phenylindole (1:1000; Dojindo), and macrophages were detected by phycoerythrin‐labeled anti‐mouse F4/80 monoclonal antibody (1:1000; BioLegend).…”
Section: Methodsmentioning
confidence: 99%
“…Cells were cultured on a 96‐well tissue culture plate, stimulated with DATS, and incubated with the water soluble tetrazolium salts‐1 (WST‐1) reagent in the Premix WST‐1 Cell Proliferation Assay System (Takara Bio) for 6 hours, 20 , 22 using a scanning multiwell spectrophotometer (440 nm; reference, 600 nm). The absorbance at 440 nm (with reference at 600 nm) was measured using a scanning multiwell spectrophotometer, which correlates to the viable cell numbers.…”
Section: Methodsmentioning
confidence: 99%
“…RNA was extracted from 1 month-study Control and Jetlag hearts at different timepoint or at light phase or H9c2 cells immediately after 48 h of transfection with siRNA targeting CLOCK using the RNeasy Mini Kit (Qiagen), and equal amount of total RNA was reverse-transcribed using ReverTra Ace qPCR RT Master Mix (TOYOBO). Real-time PCR was performed using Bio-Rad real-time PCR detection system with THUNDERBIRD SYBR qPCR mix (TOYOBO) under the following conditions: 95 °C for 10 min, followed by 40 cycles at 95 °C for 15 s and 60 °C for 45 s 55 . The gene expression of each target gene was normalized to that of GAPDH 55 .…”
Section: Methodsmentioning
confidence: 99%